2000
DOI: 10.1093/nar/28.11.2214
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an essential Schizosaccharomyces pombe gene, prp31+, that links splicing and meiosis

Abstract: We carried out a screen for mutants that arrest prior to premeiotic S phase. One of the strains we isolated contains a temperature-sensitive allele mutation in the fission yeast prp31(+) gene. The prp31-E1 mutant is defective in vegetative cell growth and in meiotic progression. It is synthetically lethal with prp6 and displays a pre-mRNA splicing defect at the restrictive temperature. We cloned the wild-type gene by complementation of the temperature-sensitive mutant phenotype. Prp31p is closely related to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…For most genes, maximum inhibition of splicing was observed 12-14 hours following addition of thiamine suggesting that depletion of Ini1 may take several hours. Although the levels of accumulation of premRNA did not reach the levels detected in the prp2-1 mutant, they were clearly above background and are similar to data published for other splicing defective mutants (Bishop et al, 2000;Burns et al, 1999;Habara et al, 2001;Shimoseki and Shimoda, 2001;Urushiyama et al, 1996). The prp2-1 mutant is unique in displaying a very strong inhibition of splicing at the restrictive temperature.…”
Section: Resultssupporting
confidence: 83%
“…For most genes, maximum inhibition of splicing was observed 12-14 hours following addition of thiamine suggesting that depletion of Ini1 may take several hours. Although the levels of accumulation of premRNA did not reach the levels detected in the prp2-1 mutant, they were clearly above background and are similar to data published for other splicing defective mutants (Bishop et al, 2000;Burns et al, 1999;Habara et al, 2001;Shimoseki and Shimoda, 2001;Urushiyama et al, 1996). The prp2-1 mutant is unique in displaying a very strong inhibition of splicing at the restrictive temperature.…”
Section: Resultssupporting
confidence: 83%
“…Database searches with the complete amino acid sequence of the human 61K protein revealed that it is a homolog of the Prp31p protein of Saccharomyces cerevisiae (25% identity, 60% similarity) and Schizosaccharomyces pombe (68% similarity). Both proteins have been shown to be essential splicing factors in yeast (Weidenhammer et al ., 1996; Bishop et al ., 2000). The regions of homology are found throughout the entire sequence and are not restricted to one particular domain (Figure 1; data not shown); thus, these proteins are potentially orthologs.…”
Section: Resultsmentioning
confidence: 99%
“…Connections between splicing and cell cycle progression have been known for several years. Mutations in genes coding for Prp proteins of S. cerevisiae or Prp homologues of S. pombe and causing cell cycle arrest were identified (Lundgreen et al , 1996; Bishop et al , 2000; Biggins et al , 2001). Recently, evidence is accumulating indicating a link between splicing and the cell cycle.…”
Section: Resultsmentioning
confidence: 99%